PENGARUH PERGANTIAN MANAJEMEN, UKURAN PERUSAHAAN, UKURAN KAP, DAN OPINI AUDITOR TERHADAP PERGANTIAN KANTOR AKUNTAN PUBLIK (Students' Journal of Accounting and Banking, 2015)
This research investigates the effect of management change, firn size, KAP size, and the auditor's opinion to auditor changes. This research was conducted in the Indonesia Stock Exchange using manufacturing companies that have gone public. The sampling method is using purposive sampling with the research period 2012-2013. It was acquired 98 companies for sample of each year with the total testing sample are 196 companies (2 years). Hypothesis testing is done by logistic regression method. The results showed that management changes , firm size, KAP size, and the auditor's opinion do not affec to auditor changes.Keywords: Auditor Changes, Management Changes, Firm Size, KAP Size, and Auditor's Opinion